Procedure for Handling 4-H Accounts: Establishing and Maintaining a County 4-H Foundation - Marilyn N. Norman; Joy C. Jordan (EDIS)
Revised! 4H5.6, a 2-page fact sheet by Marilyn N. Norman and Joy C. Jordan, explains how to establish and maintain a County 4-H Foundation, lists specific tasks and agent responsibilities, and answers questions about how to support a quality foundation. Includes additional resources. Published by the Florida 4-H Program, October 2009.